2016
DOI: 10.1038/srep25272
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of FGFBP1 signaling contributes to miR-146a-induced angiogenesis in human umbilical vein endothelial cells

Abstract: Recent microRNA expression profiling studies have documented an up-regulation of miR-146a in several angiogenesis models. However, the underlying molecular mechanism of miR-146a in the angiogenic activity of endothelial cells has not been clearly elucidated. The present study was aimed to evaluate whether miR-146a promotes angiogenesis in HUVECs by increasing FGFBP1 expression via directly targeting CREB3L1. miR-146a was over expressed in HUVECs via lentiviral-miR-146a. Expression profiling analysis found miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…One previous report found that inhibition of miR-146a led to increased capillary sprouting in both aortic ring and laser-induced choroidal neovascularization assays (Halkein et al, 2013 ). In contrast, several previous studies have found that loss of miR-146a impairs angiogenesis in vitro (Zhu et al, 2013 , 2016 ; Rau et al, 2014 ; Li et al, 2017 ), which would suggest miR-146a inhibition should impair perfusion recovery. In our hands, in vitro miR-146a inhibition attenuated both network-like formation and EC migration while there was no effect on EC survival or permeability.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…One previous report found that inhibition of miR-146a led to increased capillary sprouting in both aortic ring and laser-induced choroidal neovascularization assays (Halkein et al, 2013 ). In contrast, several previous studies have found that loss of miR-146a impairs angiogenesis in vitro (Zhu et al, 2013 , 2016 ; Rau et al, 2014 ; Li et al, 2017 ), which would suggest miR-146a inhibition should impair perfusion recovery. In our hands, in vitro miR-146a inhibition attenuated both network-like formation and EC migration while there was no effect on EC survival or permeability.…”
Section: Discussionmentioning
confidence: 76%
“…To this end, inhibition of miR-100 has been shown previously to enhance perfusion recovery following FAL (Grundmann et al, 2011 ), and we have recently determined that miR-199a inhibition is a potent enhancer of perfusion recovery and arteriogenesis following FAL in Balb/c mice (Heuslein and Price, 2017 ). Though miR-146a has been shown to be enriched in ECs in vivo (Cheng et al, 2013 ) and to regulate both endothelial activation (Cheng et al, 2013 ) and in vitro angiogenesis (Zhu et al, 2013 , 2016 ; Rau et al, 2014 ), the role of miR-146a following FAL is unknown. Here, we tested the hypothesis that miR-146a regulates angiogenesis, arteriogenesis, and perfusion recovery after FAL.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our data suggest that miR-146 mimics suppress NF-κB signaling-activated inflammation via its target genes, IRAK and TRAF6, and consequently reduce thrombosis, leading to improved peripheral tissue perfusion. Others have shown that miR-146a increases angiogenesis in human umbilical vein endothelial cells ( 44 ). Thus, the effects of miR-146a on vascularization in sciatic nerves of diabetic mice warrant further study.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have demonstrated that miR-146a enhances the angiogenic activity of endothelial cells in hepatocellular carcinoma by promoting the expression of platelet-derived growth factor receptor α [12]. In addition, miR-146a induces angiogenesis in human umbilical vein endothelial cells via upregulation of FGFBP1 signaling [13]. …”
Section: Discussionmentioning
confidence: 99%